On Strike at Hormel: The Struggle for a Democratic Labor Movement - Lederer, Norman (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "On Strike at Hormel: The Struggle for a Democratic Labor Movement," by Hardy Green.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes